Economic growth for ecological conversions: South Korean case - Lee, Hye Kyung (Environ Sci Eur, 2018)
BACKGROUND: Sprawl has been named as one of the critical reasons for the latest social problems in many parts of the world. This is particularly true for developing countries, as their national status largely depends on economic stability and interacts with the rise and decline of major cities. This study focuses on a detailed notion on environmental impact of physical expansion and answers how to specifically estimate the ecological impact of sprawl using the GIS and ecological valuation method. Especially, South Korean cities are examined to identify how development-oriented growth would affect natural stock and the ecology as a whole. RESULTS: By implementing land cover datasets and an estimation method, value transfer, the authors examine the economic losses of Korean ecological stock between 1980 and 2000. Since 1980, the society has gained a significant amount of growth in its national economics. Specifically, GDP has increased from about $40 billion to $640 billion. However, due to its rapid growth, the entire natural stock has lost about 5% of its total features, using the median economic values. If calculated with the maximum values, it is about a 7% decrease. The results indicate that $2076/person for environmental opportunity costs is estimated as a consequence of rapid urbanization. CONCLUSIONS: If we had estimated the ecological consumptions of rapid growth from the beginning and considered $2076/person for environmental opportunity costs, then the development patterns and other associated urban planning agendas would have shifted accordingly to increase the overall sustainability. Like most developing cities in the world, major cities in South Korea and the central government concentrated its main strategy on economic growth. Doing so stimulated national economy and made it possible to level up the quality of life. If this quality of life needs to be sustained for a long term, then we should focus on our usage of ecological features, as their characteristics are completely different from man-made resources.